Similar major cardiovascular outcomes between pure statin and ezetimibe-statin in comparable intensity for type 2 diabetes with extremely atherosclerotic risks - Yu-Cheng Kao (Scientific Reports, 2021)
Abstract Atorvastatin 40 mg (ATOR 40) and ezetimibe 10 mg/simvastatin 20 mg (EZ-SIM 20) have similar reductions of low-density lipoprotein cholesterol (LDL-C) but cardiovascular (CV) outcomes between these two therapies are unclear. Our real-world cohort study is to test the hypothesis of pleiotropic effects of purely higher dose statin on CV outcomes beyond similar reductions of LDL-C, especially for extremely CV risk patients. Between January 1, 2007 and December 31, 2013, a total of 3,372 patients with type 2 diabetes mellitus (T2DM) admitted due to acute coronary syndrome (ACS) or acute ischemic stroke (AIS) were selected as the study cohort from the Taiwan National Health Insurance Research Database. Clinical outcomes were evaluated by ATOR 40 group (n = 1686) matched with EZ-SIM 20 group (n = 1686). Primary composite outcome includes CV death, non-fatal myocardial infarction, and non-fatal stroke. Secondary composite outcome includes hospitalization for unstable angina (HUA), percutaneous coronary intervention (PCI), and coronary artery bypass grafting (CABG). With a mean follow-up of 2.4 years, no significant difference of primary composite outcome was observed between ATOR 40 and EZ-SIM 20 groups (subdistribution hazard ratio [SHR], 1.09; 95% confidence interval [CI], 0.95–1.25). Nevertheless, ATOR 40 group had lower risks of HUA (SHR, 0.50; 95% CI, 0.35–0.72), PCI (SHR, 0.82; 95% CI, 0.69–0.97) and CABG (SHR, 0.62; 95% CI, 0.40–0.97) than EZ-SIM 20 group. For T2DM patients after ACS or AIS, ATOR 40 and EZ-SIM 20 had similar major CV outcomes, which still supported the main driver for CV risk reductions is LDL-C lowering.